(untitled) (Journal of Applied Oral Science, 2009)
Glass ionomer based materials are clinically popular in several areas of restorative dentistry, but restoration of cervical lesions has proven particularly successful. Various etiologies, conformations, locations and structural characteristics make non-carious cervical lesions more challenging to adhesive restorative procedures and marginal seal in the long run. Due to their characteristics, glass ionomer cements (GICs) have precise indication for these cases. Moreover, the use of a GIC base underneath composite resin, the so-called "sandwich" or mixed technique, allows associating the good characteristics of composite resins and GICs, and has been considered quite useful in the restoration of non-carious cervical defects. The aim of this paper is to critically review the literature and discuss peculiar features of GICs regarding their role in the restoration of non-carious cervical lesions.